KANDUNGAN BETA KAROTEN DAN AKTIVITAS PENANGKAPAN RADIKAL BEBAS TERHADAP DPPH (1,1-difenil 2-pikrilhidrazil) EKSTRAK BUAH BLEWAH (Cucumis melo var. Cantalupensis L) SECARA SPEKTROFOTOMETRI UV-VISIBEL - Aprilia Kusbandari; Hari Susanti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
Cantaloupe (Cucumis melo var. Cantalupensis L.), a fruit containing some compounds, have activity to protect human body from free radical. The beta carotene (provitamin A) was recognized as antioxidant compound. Antioxidants could protect the body from cardiovascular damage caused by free radical. The aims of this study was to determine the levels of beta carotene and antioxidant activity (IC50) from Cucumis melo var. cantalupensis L. extract using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Cantaloupe was extracted using n-hexan-acetone-methanol ratio (2: 1: 1). Identification of beta carotene was performed using 25% antimony trichloride reagent followed by TLC and UV-Vis spectrum test compared with beta carotene as standard. The content of beta carotene and free radical scavenging activity was measured spectrophotometrically at 425 nm. The beta carotene level of cantaloupe was 3.171 0.150 %. The antioxidant activity, presented as IC50 value of cantaloupe extract, was 12.1370.44 g/mL and the antioxidant activity of standard beta carotene was 2.15 0.172 g/mL. The cantaloupe extract contained beta carotene compunds but the antioxidant activity of extract was lower than beta carotene standard.